Plasma oscillations propagating along the magnetic field in the Uragan-2M torsatron - Skibenko, A.I.; Prokopenko, A.V.; Pinos, I.B. (Вопросы атомной науки и техники, 2013)
The spectral and correlation analysis were applied to study interferometry date measured in two toroidally spaced transverse sections. The oscillation frequency increase for higher magnetic field and decrease with density rising which cold be attributed with existance of Alfven eigenmodes. Calculated frequency values cold be higher that from spectral analysis. This may be due to presence of impurities in plasma.